Bioremediation Potential: Discovering Naphthalene-Degrading Microbes in Iraqi Contaminated Soil - Zahraa M. Abdulhussein; Amal A. Hussein (International Journal of Pathogens, 2024)
A polycyclic aromatic hydrocarbon, napthalene is an environmental contaminant with a slow rate of disintegration. Biological treatment by microbes present in contaminated places is the most important of the several approaches applied to remove it from the environment. At depths of 5 to 10 cm, soil samples were collected from areas polluted by oil near the Al-Dora and Sheikh Omar refineries. Nutrient agar was cultured with 0.1 ml of each dilution, which ranged from 10-1 to 10-8. Twenty separate bacterial colonies were isolated and cultured on petri dishes using Bushnell Haas Media agar with naphthalene as the sole carbon and energy source. For seven days, the cultures were kept in an incubator set at 37°C. Two dishes were subsequently examined to determine the locations of the growth. Two separate cultures were grown in liquid Bushnell Haas Media and then incubated in a shaker incubator for seven days at 37°C and 150 rpm. Next, High-Performance Liquid Chromatography (HPLC) was employed to measure the amount of naphthalene degraded by these microorganisms. The most effective bacterial isolates were identified using the VITEK 2 technology. The naphthalene degradation rates of Serratia ficaria and Bacillus subtilis were rather high; Serratia ficaria at 85.16 percent and Bacillus subtilis at 93.36 percent, respectively.
Keywords: Bacteria; Degrading; Naphthalene; Pollution; soil